Sovereignty and Responsibility in Global Refugee Protection and Humanitarian Intervention in the 21st Century - Zayzda, Nurul Azizah (Insignia: Journal of International Relations, 2015)
AbstractThis paper is concerned on the interlinking politics in refugee protection and humanitarian intervention as well as the trends of developments in refugee protection that has been undermined especially in a number of developed countries. In international protections, sovereignty always appear as a major debate since protections involve interference by external forces (in humanitarian intervention) or arrivals of external populations (in refugee protection). The sense of responsibility, referring to the political willingness to provide protection or assistance have been influenced by the understanding on sovereignty. The aim of this paper is to explain how the concepts have been contested through practices of refugee protection and responsibility to protect. In order to demonstrate the issue of sovereignty and responsibility at hand, this paper departs from the discussion of the two concepts as found in the historical accounts of the protection regimes which are refugee protection and the humanitarian intervention. The following part discusses the recent development of the two regimes of international protection. Within each part, the notion of sovereignty and responsibility are assessed from the practices of the two regimes. From the discussion, it can be understood that the ways these concepts were produced and contested reflect the presence of a bigger framework namely politics of human rights which tend to be dominated by the interests of big political power. Keywords: sovereignty, responsibility, human rights, refugee protection, humanitarian intervention, responsibility to protect. AbstrakTulisan ini ingin mendalami keterkaitan politik HAM dalam perkembangan perlindungan pengungsi lintas batas dan intervensi kemanusiaan serta dampaknya berupa kecenderungan membatasi laju pengungsi di sejumlah negara maju. Dalam perlindungan internasional, kedaulatan selalu muncul sebagai debat utama karena perlindungan masyarakat terdampak melibatkan keterlibatan kekuatan/militer eksternal (dalam intervensi kemanusiaan) atau kedatangan populasi eksternal (dalam perlindungan pengungsi). Rasa tanggung jawab, merujuk kepada kemauan politis untuk memberikan perlindungan atau bantuan, dipengaruhi oleh bagaimana kedaulatan ini dipahami. Tujuan tulisan ini adalah menjelaskan bagaimana kedaulatan dan tanggung jawab dikontestasi melalui praktek perlindungan pengungsi lintas batas dan intervensi kemanusiaan. Untuk menunjukkan isu kedaulatan dan tanggung jawab, tulisan ini berangkat dari pembahasan mengenai kedua konsep yang terdapat dalam sejarah dari rezim perlindungan pengungsi lintas batas dan intervensi kemanusiaan. Bagian berikutnya membahas perkembangan dari dua rezim internasional perlindungan bagi masyarakat terdampak. Di bagian ini, gagasan kedaulatan dan tanggung jawab harus dipelajari dari praktek-praktek dua rezim perlindungan internasional tersebut. Dari diskusi yang ada, dapat dipahami bahwa konsep yang diproduksi dan dikontestasi merupakan bagian dari kerangka yang lebih besar yaitu politik HAM yang cenderung masih didominasi oleh kepentingan kelompok negara dengan kekuatan politik yang besar. Kata-Kata Kunci: kedaulatan, tanggung jawab, politik HAM, perlindungan pengungsi lintas batas, intervensi kemanusiaan.